Use of white light therapy in treatment of non-motor symptoms in Parkinson’s disease - Góralczyk, Wanesa; Mikos, Eryk; Kanon, Karol (Journal of Education, Health and Sport, 2021)
Introduction. Parkinson’s disease (PD) is a progressive neurodegenerative disorder, associated with selective loss of neurons in the substantia nigra. Parkinson’s disease revealed by motor and non-motor symptoms. Alternative therapies for cure non-motor symptoms are searched. One of them can be white light therapy, which is based on taking samples of light specified illuminance, time of day, period and head-to-light distance. Brief description of the state of knowledge. The purpose of white light therapy is stabilization of the circadian melatonin secretion and improvement of circadian rhythmicity. Morning white light exposure allows to accelerate the circadian rhythm and is effective in cure of depression disorders. In turn evening light exposure is used to delayed the circadian rhythm and treat early awaking insomnia. The effectiveness of treatment by white light therapy other neurological and neuropsychiatric disease as depression or sleep disorder is well-documented. Conclusions. White Light Therapy is a safe, easy to use, and inexpensive non-pharmacological treatment option with rare side effects. Research shows that light has a significant therapeutic effect on a broad spectrum of symptoms, such as tremor, bradykinesia, rigidity, insomnia. However more evidence is needed to define specific dose of light for treatment non-motor symptoms Parkinson’s disease and the regime of its intake (length of irradiation, time of day, distance between the head and the light source).